PERSPEKTIF PENDIDIKAN ISLAM TENTANG REKONSTRUKSI REVOLUSI KULTURAL SUMBER DAYA MANUSIA - Isnaini, Muhammad (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Reconstruction or the strive of rebuilding and developing human resources should not only focused on the improvement of physical skill, but also non-physic sectors like values system, religious norms, and moral values. One of the causes of multidimensional crisis faced by Indonesian people is stemming from their own mistakes in which they give more emphasis on physical development than non-physic. It has to be considered a valuable lesson for society, especially for education organizers. Big physical capital does not guarantee that it can prevent, save, or brighten Indonesian people from crisis when non-physic side of human resources does not become the priority.Copyright © 2013 by Al-Talim All right reservedDOI: 10.15548/jt.v20i2.38